Deconstructing Rotterdam’s modern city centre - van der Hoeven, Frank (project baikal, 2013)
In the 20th century, the Dutch city of Rotterdam was radically transformed from a historic town into a modern city, becoming the selfacclaimed ’city of architecture’, home to international architectural design offices, publishers and institutions. Although it is already 60 years after the destruction of the Rotterdam inner city, the city still struggles to be the vibrant, rigorous urban environment it needs to be in order to attract the so-called creative class. This article provides a contextual overview of the transformations of a number of key public spaces that are symbolic for the challenges the city faces. After the post-war reconstruction the city continue to transform itself beyond modernism.